Effects of exercise modality combined with moderate hypoxia on blood glucose regulation in adults with overweight - Tee, Chris Chow Li; Chong, Mee Chee; Cooke, Matthew B.; Rahmat, Nurhamizah; Yeo, Wee Kian; Camera, Donny M. (Frontiers in Physiology, 2024)
Purpose: This study aimed to investigate the combined effects of moderate hypoxia with three different exercise modes on glucose regulation in healthy overweight adults.Methods: Thirteen overweight males (age: 31 ± 4 years; body fat 26.3 ± 3.2%) completed three exercise trials in a randomized crossover design involving 60 min cycling exercise at 90% lactate threshold (LOW), sprint interval training (20 x 4s all-out; SIT) and lower limb functional bodyweight exercises (8 sets of 4 x 20 s; FEX) under moderate hypoxia (FiO2 = 16.5%). Post-exercise oral glucose tolerance test (OGTT) was performed following each trial. Heart rate, oxygen saturation (SpO2), physical activity enjoyment scale (PACES), and perceptual measures were recorded during each exercise session. Venous blood was collected pre-, immediately post-, and 24 h post-exercise and analysed for plasma glucose and insulin, incremental area under curve (iAUC), and circulating microRNA expression (c-miRs-486-5p, -126-5p, and -21-5p). Interstitial glucose concentrations were measured using continuous glucose monitoring (CGM).Results: Post-exercise OGTT iAUC for plasma glucose and insulin concentration were lower in SIT and LOW vs control (p < 0.05) while post-exercise interstitial glucose iAUC and c-miRs were not different between exercise modes. Heart rate was greater in SIT vs LOW and FEX, and FEX vs LOW (p < 0.05), SpO2 was lower in SIT, while PACES was not different between exercise modes. Perceptual measures were greater in SIT vs LOW and FEX.Acute SIT and LOW under moderate hypoxia improved post-exercise plasma insulin compared to FEX exercises. Considering SIT was also time-efficient, well tolerated, and enjoyable for participants, this may be the preferred exercise modality for improving glucose regulation in adult males with overweight when combined with moderate hypoxia.